GAMBARAN MOTIVASI ORANG TUA TERHADAP PEMBERIAN IMUNISASI DASAR LENGKAP PADA ANAK < 1 TAHUN DI MASA PANDEMI COVID-19 - Oktifani, Latifa; Novayelinda, Riri; Hasanah, Oswati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
The COVID-19 pandemic has caused changes in the way parents view the provision of complete basic immunization for children. This study intended to determine the motivation of parents on giving complete basic immunization to children <1 year of age during the COVID-19 pandemic. This study was a quantitative study that took a simple descriptive design. The research site was in the working area of Sidomulyo Public Health Center Outpatient. The research sample consisted of 95 respondents who were taken using purposive sampling technique. The measuring instrument used was a motivation questionnaire that had been declared valid and reliable, where the type of analysis applied was univariate analysis. As many as 74 respondents (77.9%) or the majority of them had strong motivation, 20 respondents (21.1%) had moderate motivation, and 1 respondent (1.1%) had weak motivation. In the current COVID-19 pandemic, the motivation of parents in giving complete basic immunization to children is very important so that they are willing to provide it. Immunization is very necessary to fully support the basic needs of children to increase their immunity and prevent illness caused by disease and the possibility of disability or death. Keywords: Children, COVID-19, Immunization, Motivation